MELIHAT JIN PERPSEKTIF AT-TAHRIR WA AT-TANWIR DAN RUH AL-BAYAN FI TAFSIR AL-QUR'AN : Studi Atas Penafsiran Ibn Asyur dan Ismail Haqqi terhadap al-A'raf ayat ayat 27 - Al Zhafir, Turkey (Jurnal Moderasi, 2024)
Abstract This article tries to discuss the views of two contemporary mufassirs, Muhammad Thahir Ibn Ashur and Ismail Haqqi through two different manhaj (adaby and isyari) in their major works, at-Tahrir wa at-Tanwir and Ruh al-Bayan as a form of response to the phenomenon of indigo children who are considered capable of seeing invisible creatures (jinn). The conclusion that results from both interpretations is the same, namely that humans cannot see jinn or subtle beings with the naked eye although there are differences in illat or reasons for the inability of human vision to achieve it. Keywords: Indigo, Jinn, Ibnu Ashur, Ismail Haqqi